The notion of author in and from M. Bakhtin's work - Marchezan, Renata Coelho [UNESP] (My University, 2015)
Electing contrasts with other theorists, Barthes among them, as well as confluences with trends of philosophical thought, in which case we emphasize concepts of world of life and world of culture, we go back to the reflection upon the notion of author and subject in the work of M. Bakhtin. In this path, we show the relation of these notions of author as well as subject with other important concepts of Bakhtinian thought and, while examining Bakhtin's whole work, we end by emphasizing the development of the theorist's works, as well as the principles on which they have always been based, as a whole. Finally, we expect to highlight that the concepts of world of life and world of culture, which disclose an important philosophical affiliation of Bakhtin, similar to the one verified in G. Simmel, particularize Bakhtin's contributions, also in relation to the structuralist paradigm in opposition to which we started the study.
Keywords: Author; Depersonalization; Subject; World of culture; World of life